Segmental pigmentation disorder: A rare form of cutaneous dyspigmentation - Kamran Balighi; Kambiz Kamyab; Arghavan Azizpour; Elahe Amini; Shabnam Fahim (Babol University of Medical Sciences, 2017)
Background: Segmental pigmentation disorder (SegPD) is a rare type of cutaneous dyspigmentation. This hereditary disorder, first described some 20 years ago, is characterized by hypo and hyperpigmented patches on the trunk, extremities and less likely on the face and neck. These lesions are considered as a type of checkerboard pattern. Case Presentation: Herein, we present a 26-year-old male who presented with hyperpigmented patches on his trunk, neck and upper extremities. Considering the clinical and histopathological findings, the diagnosis of SegPD was confirmed. Conclusion: SegPD is a somewhat neglected entity which should be considered in differential diagnosis of pigmentation disorders.